From UDL to AEN: Prospects of teaching and implementing new curricular languages in Irish schools - Wang, Hongfei (My University, 2023)
With the implementation of Languages Connect, Ireland’s Strategy for Foreign Languages in Education, four new foreign languages have been introduced into the Leaving Certificate curriculum, namely Polish, Lithuanian, Portuguese and Mandarin Chinese. The pitches of the curriculum specifications vary from pre-A1/A1 to A2/B1 as in the Common European Framework of Reference for Languages, while the courses are open to any student regardless of language background and proficiency. It is a norm for the new language classrooms to have both heritage and non-heritage students learning together. Therefore, Universal Design for Learning (UDL) was identified by teachers of the new curricular languages to be one of the main and consistent challenges for teaching and learning as well as for curriculum implementation. On the other hand, the provision of new languages has also shed light on the understanding of Additional Educational Needs (AEN). It is reported particularly by teachers of Mandarin Chinese that students with diagnosed dyslexia do not necessarily perform inadequately in Mandarin courses. On the contrary, in a number of cases, these students outperform other students in the perception and production of Mandarin scripts. It is time to review the understanding of AEN and the perception of its impact on language learning with a broader view of the language landscape and in the context of UDL.
UDL International Symposium:Learning Together
Keywords: UDL, AEN, Language Policy, Mandarin Chinese; LANGUAGE; LANGUAGE DISORDER; Teaching and learning; Education